Comparative evaluation of marginal adaptation of two resin-based sealers: A scanning electron microscopic study - Prashant Moogi; Anjum Sayyad; Vishnu Rathore; Surabhi Ghosh; Shweta Ambalia; Aditi Amin (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim of the study was to evaluate the marginal adaptation of two epoxy resin-based sealers to dentin. Materials and Methods: Forty freshly extracted human single-rooted mandibular premolar teeth with completely formed apices were selected. Teeth were decoronated, and root canals were instrumented. The specimens were divided equally into two groups: (1) Group 1 (n = 20) - Teeth obturated with gutta percha and Perma Evolution. (2) Group 2 (n = 20) - Teeth obturated with gutta percha and AH Plus sealer. Later, samples were vertically sectioned using diamond disk, and marginal adaptation of sealers was evaluated at coronal, middle, and apical halves using scanning electron microscopy, and marginal gap values were recorded. Results: Both the sealers produced a marginal gap to a certain extent. Perma Evolution exhibited an average marginal gap of 6.02 ± 4.81, followed by AH-Plus with 6.56 ± 4.73. Conclusion: As the marginal gaps between dentin sealers were seen to be minimum in Perma Evolution, we conclude that Perma Evolution is better adapted to root canal dentin than AH-Plus sealer.